How Target-Sequence Enrichment and Sequencing (TEnSeq) Pipelines Have Catalyzed Resistance Gene Cloning in the Wheat-Rust Pathosystem - Zhang, Jianping; Zhang, Peng; Dodds, Peter; Lagudah, Evans (Frontiers in Plant Science, 2020)
The wheat-rust pathosystem has been well studied among host-pathogen interactions since last century due to its economic importance. Intensified efforts towards cloning of wheat rust resistance genes commenced in the late 1990s with the first successful isolations published in 2003. Currently, a total of 24 genes have been cloned from wheat that provides resistance to stem rust, leaf rust, and stripe rust. Among them, more than half (15) were cloned over the last four years. This rapid cloning of resistance genes from wheat can be largely credited to the development of approaches for reducing the genome complexity as 10 out of the 15 genes cloned recently were achieved by approaches that are summarized as TEnSeq (Target-sequence Enrichment and Sequencing) pipelines in this review. The growing repertoire of cloned rust resistance genes provides new tools to support deployment strategies aimed at achieving durable resistance. This will be supported by the identification of genetic variation in corresponding Avr genes from rust pathogens, which has recently begun. Although developed with wheat resistance genes as the primary targets, TEnSeq approaches are also applicable to other classes of genes as well as for other crops with complex genomes.